2021
DOI: 10.1101/2021.01.12.426411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A method for the efficient iron-labeling of patient-derived xenograft cells and cellular imaging validation

Abstract: There is momentum towards implementing patient-derived xenograft models (PDX) in cancer research to reflect the histopathology, tumour behavior, and metastatic properties observed in the original tumour. These models are more predictive of clinical outcomes and are superior to cell lines for preclinical drug evaluation and therapeutic strategies. To study PDX cells preclinically, we used both bioluminescence imaging (BLI) to evaluate cell viability and magnetic particle imaging (MPI), an emerging imaging techn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Knier et al demonstrated the first method for the efficient iron-labelling of PDX cells, which was also the first successful iron-labelling of breast cancer cells derived from patient brain metastases. 271 Utilising bioluminescence imaging (BLI) to evaluate cell viability, and MPI for detection and quantification of SPION content, they demonstrated sensitive longitudinal tracking of pre-labelled F2–7 PDX cells with MPIOs, where the signals indicate cell viability and tumor proliferation.…”
Section: Primary Biomedical Applications Of Mpimentioning
confidence: 99%
“…Knier et al demonstrated the first method for the efficient iron-labelling of PDX cells, which was also the first successful iron-labelling of breast cancer cells derived from patient brain metastases. 271 Utilising bioluminescence imaging (BLI) to evaluate cell viability, and MPI for detection and quantification of SPION content, they demonstrated sensitive longitudinal tracking of pre-labelled F2–7 PDX cells with MPIOs, where the signals indicate cell viability and tumor proliferation.…”
Section: Primary Biomedical Applications Of Mpimentioning
confidence: 99%